2010
DOI: 10.1177/0021955x10367703
|View full text |Cite
|
Sign up to set email alerts
|

Silane-functionalized Flame-retardant Aluminum Trihydroxide in Flexible Polyurethane Foam

Abstract: Flexible polyurethane (PU) foams are easily ignitable and show a high burning velocity, mainly due to their high surface area-to-mass ratio and high air permeability. Consequently, flame retardants such as halogenated compounds are applied. However, the use of halogenated flame retardants is not considered beneficial in transport applications, for example, aviation or automobile, in part due to the high smoke generation. Solid nonhalogenated flame retardants, for example, aluminum trihydroxide (ATH), are known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 11 publications
2
19
0
Order By: Relevance
“…This effect can be explained by the increase in the foaming system viscosity caused by the presence of the fillers,24, 27 the nucleation effect of the microcapsules,27 the higher amount of mass that has to be lifted by the same expanding gas generated during the foaming process, and by its less cell expansion 24. The lower cell expansion is attributed to the absorption by the PCM of part of the heat released during the chemical reactions of this process what decreases the reaction temperature and reduces the expansion volume of the CO 2 cell gas 24. On the other hand, Figure 9 shows a comparison of the final heights and foaming rates of these two microcapsules types with those obtained with mSD‐(LDPE·EVA‐RT27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect can be explained by the increase in the foaming system viscosity caused by the presence of the fillers,24, 27 the nucleation effect of the microcapsules,27 the higher amount of mass that has to be lifted by the same expanding gas generated during the foaming process, and by its less cell expansion 24. The lower cell expansion is attributed to the absorption by the PCM of part of the heat released during the chemical reactions of this process what decreases the reaction temperature and reduces the expansion volume of the CO 2 cell gas 24. On the other hand, Figure 9 shows a comparison of the final heights and foaming rates of these two microcapsules types with those obtained with mSD‐(LDPE·EVA‐RT27).…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were reported by Javni et al22 who observed that Cloisite Na + (natural montmorillonite) and nano‐silica with a hydrophilic surface increased hardness and compression strength of the foams, whereas Cloisite_10A modified with a quaternary ammonium salt decreased the modulus, hardness, and compression strength. Additionally, results reported by Cao et al,23 König et al,24 and Harikrishnan et al25 indicated that other fillers such as organically modified montmorillonite, aluminum trihydroxide particles, or carbon nanofibers increased the compression strength of polyurethane foams.…”
Section: Introductionmentioning
confidence: 93%
“…Flame retardant polyurethanes foams have been prepared by addition of various flame retardant compounds such as compounds containing phosphorus and/or nitrogen groups, expendable graphite, MgO, and Al 2 O 3 . It was observed that expandable graphite and nitrogen‐based derivatives require higher loading as additive to achieve decent flame retardancy .…”
Section: Introductionmentioning
confidence: 99%
“…The addition of FR polyol showed no significant change in the compressive strengths of the foams [Figure (b)]. Usually, AFRs such as dimethyl methyl phosphonate (DMMP), 2,2‐diethyl‐1,3‐propanediol phosphoryl melamine (DPPM), melamine, and expandable graphene tend to adversely affect the compressive strength of the foams . In fact, the addition of MCO–DEAP polyol showed slightly improved compressive strength of the foams .…”
Section: Resultsmentioning
confidence: 99%